(untitled) (GYMNASIUM, 2017)
The purpose of this paper was to identify and select the most effective massage methods to fight against the effects of occupational stress. The research was conducted on a number of 10 female patients, having desk jobs and working overtime beyond the eight hour- program for carrying out their duties. The therapeutic intervention consisted of applying classic relaxation massage combined with reflexotherapy, shiatsu and stretching. The analysis of results in the three evaluation tests (Pichot’s fatigue scale, the Profile of emotional distress, survey on the stress level) showed there is a significant reduction of the scores in the final testing as compared with the initial one, which means a visible improvement in the occupational stress level; this is seen by a higher work capability, bigger focus and more energy in all day-to-day activities.